La visión de la historia en las obras de Ricardo Piglia - Cselik, Ágnes (Verbum – Analecta Neolatina, 2014)
Can the narrative version of history replace the real one? Does objective history exist or is everything fictious, and do we choose some version and declare it to be the real one? In the works of Ricardo Piglia the series of personal, private stories are interleaved with the writing process, with the theory of history and most importantly, with hypothetical history. For Ricardo Piglia, the act of writing is an activity which allows one to create different versions and different drafts; this is impossible with history that one lives in, history which is experienced in person. In this paper, I analyze Piglia’s method of converting tangible reality and a history situation defined in pure literary fiction. The account approaches the problem from the viewpoint of the protagonists, stories and the complete work of the author.